Two years imprisonment in Burma (1824-1826) a personal narrative of Henry Gouger - Gouger, Henry (Collection Burmese historical reprint series, 2003)
Gouger, a British merchant, witnessed at first hand the traumatic effects of the first Anglo-Burmese war on the Court and population of the Kingdom of Ava. He was jailed in Let Ma Yoon prison in Ava where he spent two years on death row, along with six others suspected of being spies, one of whom was Dr. Adoniram Judson, whose life and work is well documented elsewhere. The author offers a unique account of a crucial period in the history of Burma, which is valuable for historians, scholars, researchers and students alike. Having rendered his experiences into a book 35 years after the events, Gouger takes care to explain the local context, providing carefully selected and informative observations, with much thought for the Burmese themselves.